Treatment of post-traumatic elbow deformities in children with the Ilizarov distraction osteogenesis technique - Cenk Özkan; Mehmet Ali Deveci; Mustafa Tekin; Ömer Sunkar Biçer; Kadir Gökçe; Mahir Gülşen (Acta Orthopaedica et Traumatologica Turcica)
Objective: The present study assessed functional and radiographic outcomes of distraction osteogenesis treatment of post-traumatic elbow deformities in children. Methods: Eight children were treated between 2008 and 2013 for post-traumatic elbow deformities using distraction osteogenesis. Mean age at time of operation was 10.9 years. Six patients had varus and 2 had valgus deformity. Magnitude of correction, fixator index, complications, carrying angle, and elbow range of motion were assessed. Functional results were graded according to protocol of Bellemore et al. Results: Mean follow-up was 43 months. Mean preoperative varus deformity in 6 patients was 29.2° and valgus deformity in 2 patients was 28.5°. Preoperative flexion and extension of elbow were 123.8° and −10.6°, respectively. Mean carrying angle was 9° valgus at last follow-up. Mean flexion and extension were 134.4° and −6.0°, respectively. Change in carrying angle was statistically significant (p = 0.002). There were 2 grade 1 pin tract infections and 1 diaphyseal fracture of humerus. Functional outcome was rated excellent in 7 patients and good in 1 patient. Conclusion: Ilizarov distraction osteogenesis is a valuable alternative in treatment of elbow deformities in children. The surgical technique is simple and correction is adjustable. Gradual correction prevents possible neurovascular complications and minimally invasive surgery produces less scarring. Compliance of patient and family is key factor in the success of the outcome. Level of evidence: Level IV, therapeutic study Keywords: Cubitus varus, Cubitus valgus, Distraction osteogenesis, Ilizarov technique